2017
DOI: 10.1186/s13071-017-2476-y
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluations of the immediate and sustained efficacy of lotilaner (Credelio™) against four common species of ticks affecting dogs in North America

Abstract: BackgroundEffective control of tick infestations on dogs is important to reduce the risk of transmission of bacterial, viral, and protozoal pathogens. Laboratory studies were initiated to determine the efficacy of lotilaner against common ticks infesting dogs in the United States.MethodsEight studies investigated the efficacy of lotilaner against ticks. In two studies dogs were infested with both Dermacentor variabilis and Rhipicephalus sanguineus: one additional study was completed for each of these species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…A report of a series of studies involving experimental infestations with commonly occurring European ticks showed that lotilaner efficacy remained at least 95% through 35 days post-treatment and a field study across three European countries subsequently confirmed lotilaner effectiveness against field challenge [ 18 , 23 ]. Similar efficacy was reported following induced infestations of commonly occurring ticks in North America [ 24 ]. As in this study, experimental infestation studies typically involve assessments at 48 h post-treatment, and 48 h after subsequent weekly challenges.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…A report of a series of studies involving experimental infestations with commonly occurring European ticks showed that lotilaner efficacy remained at least 95% through 35 days post-treatment and a field study across three European countries subsequently confirmed lotilaner effectiveness against field challenge [ 18 , 23 ]. Similar efficacy was reported following induced infestations of commonly occurring ticks in North America [ 24 ]. As in this study, experimental infestation studies typically involve assessments at 48 h post-treatment, and 48 h after subsequent weekly challenges.…”
Section: Resultssupporting
confidence: 78%
“…For instance, there are only two reports of afoxolaner efficacy against A. americanum - in one of these at 24 h post-infestation afoxolaner efficacy was less than 80% from Day 14 through Day 30 while under the same conditions sarolaner efficacy remained at greater than 90% until Day 28 [ 22 ]. Studies assessing lotilaner efficacy against A. americanum at 48 h post-treatment and post infestation have demonstrated efficacy of 100% throughout, except at nine days post-treatment when efficacy was 99% [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas 10 µM ivermectin treatment killed 100% of adult lice after 24h, we obtained the same result with 10 µM lotilaner in only 3 hours following exposure. This fast activity is in accordance with the 4h-12h needed to kill ticks and fleas in lotilaner treated dogs [79,80]. In contrast, neither ivermectin nor lotilaner were found to have a pediculicidal activity on nits.…”
Section: From Dog To Human: the Future For Isoxazoline Insecticides Asupporting
confidence: 80%